2016
DOI: 10.1177/0886260516633688
|View full text |Cite
|
Sign up to set email alerts
|

Social Workers’ Reflections on the Therapeutic Encounter With Elder Abuse and Neglect

Abstract: The aim of this qualitative study was to explore social workers' reflections on their experience of the therapeutic encounter with victims and perpetrators of elder abuse and neglect. The research questions were as follows: How do social workers tune themselves toward the therapeutic encounter with elder abuse? How do they position themselves vis-à-vis the clients? How do social workers describe the meaning of the intervention both for the clients and for themselves? What is the added value of the therapeutic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Moreover, for some of the staff members, the consequences of violent incidents spilled over into some of their personal and familial space, which impaired their ability to separate home from work, to the point of turning their family members into secondary victims, resulting in further stress. This was comparable to experiences of professionals who treated abused women and older people, and whose deep shock from the encounter with these victims spilled over into their private life sphere, affecting the professionals’ own intimate relationships (Band-Winterstein, Goldblatt, & Alon, 2014; Goldblatt, 2009; Goldblatt, Band-Winterstein, & Alon, 2018; Goldblatt & Buchbinder, 2003).…”
Section: Discussionmentioning
confidence: 66%
“…Moreover, for some of the staff members, the consequences of violent incidents spilled over into some of their personal and familial space, which impaired their ability to separate home from work, to the point of turning their family members into secondary victims, resulting in further stress. This was comparable to experiences of professionals who treated abused women and older people, and whose deep shock from the encounter with these victims spilled over into their private life sphere, affecting the professionals’ own intimate relationships (Band-Winterstein, Goldblatt, & Alon, 2014; Goldblatt, 2009; Goldblatt, Band-Winterstein, & Alon, 2018; Goldblatt & Buchbinder, 2003).…”
Section: Discussionmentioning
confidence: 66%
“…In terms of practitioner responses to older survivors, this can have specific consequences in practice delivery. As Goldblatt, Band-Winterstein, and Alon (2016) point out, “In intervention with young women, social empowerment is the central principle based on social ideology that maintains that women are confident, capable of taking responsibility for their own fate and making a change in their lives” (p. 14). However, ageist constructions of older people as weak and vulnerable based on a perception of aging as a process of decay, decline, and deterioration ( Jones & Powell, 2006 ) may affect the type of intervention offered and/or the success of support services.…”
Section: Discussion and Implications For Policy And Practicementioning
confidence: 99%
“…The study reported here adopts a theoretical framework informed by feminist criminology (Burgess-Proctor, 2006) and critical feminist gerontology (Ray & Fine, 1999), paying attention to the distinctive experiences of older women and older men. Garner (2014) highlights the similarities between gerontology and feminist theories. Common goals include the development of social consciousness about inequities, utilization of theories and methods that accurately depict life experiences, and promotion of change in conditions that negatively affect older people or women.…”
Section: The Studymentioning
confidence: 99%
“…This might explain in part why 22 of the 30 social workers approached for this pilot project were not interested in participating as they might have felt they did not need help with screening. A qualitative study by Goldblatt, Band-Winterstein, and Alon (2018) exploring the social workers’ reflections on their experience of the therapeutic encounter with victims and perpetrators of older adult mistreatment described that a maturation process actually occurred in the professional as well as personal life of the social workers as they dealt with these types of cases. This also supports the hypothesis that less experienced social workers might benefit more from a screening tool than experienced workers as they might need more structure and support for screening.…”
Section: Discussionmentioning
confidence: 99%